PEMBUATAN PETA DESA AIR MERAH KECAMATAN CURUP TENGAH KABUPATEN REJANG LEBONG BENGKULU (Jurnal AbdiMas Nusa Mandiri, 2024)
Maps are complex data sets containing information on the location and objects of an area. Maps can show the distribution of various things on Earth, such as settlement patterns, mountains and others. ArcGIS is software that can be used in making village maps. Air Merah village is a village in Curup Tengah sub-district, Bengkulu, which until now has not had complete mapping for the area. The purpose of this service is to help present village data that can be accessed as spatial data information in planning development progress in Air Merah Village. Community service is carried out in stages of visiting the village head's office for administrative processes, conducting discussions with the team, collecting data through field surveys and interviews, making maps, and discussing the results of thematic maps, as well as holding a presentation to discuss the results of the map and handing over map printouts to village officials. This service activity was attended by lecturers, partners and students who were involved in all series of services both in the field and discussions, so as to produce village information maps. Based on the results of field surveys and modeling, Air Merah Village has an area of ± 10.7789 km2 and is located at latitude longitude -3.4801, 102.556365. Map making has received a positive response from the surrounding community and is expected to be able to provide location information and improve the inventory of Air Merah Village.
Keywords: air merah village; arcGIS; community service; curup bengkulu; map